The Implementation of Infant and Young Children Feeding Counseling - Faisal, Elvyrah; Hafid, Fahmi; Kusumawati, Dwi Erma; Nasrul, Nasrul; Jurana, Jurana (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Counseling is an important part of successful infant and young child feeding (IYCF). Optimal IYCF is a key area for improving child survival and promoting healthy growth and development. AIM: The purpose of this study is to determine the characteristics and to provide an overview of the input, process, and output components of IYCF counseling in the Central Sulawesi stunting area. MATERIALS AND METHODS: This type of research is a semi-quantitative study which describes the knowledge and abilities of counselors. The population in this study were nutrition officers, midwives, and cadres who had received IYCF training and had followed the orientation of the IYCF module for at least 30 h in stunting focus locations. The sample in the study was counselors who received training in three subdistricts of Central of Sulawesi. RESULTS: The informants were 14 IYCF counselors. All respondents were female, aged 22–48 years. The method of counseling is by the counselor visiting pregnant women/mothers of toddlers/caregivers directly and face to face. In general, inadequate counseling room facilities are the barrier faced by counselors. Training was only limited to orientation and there was no post-training monitoring. The activities carried out by the counselor are in the range of 70–86%. Benefit of giving counseling for IYCF is that mothers will know nutritional status of their children. IYCF increases knowledge about breastfeeding better than milk formulas, the right type and age of feeding. The training has referred to the module referring to the WHO/UNICEF module which is presented in 37 h of field lessons. CONCLUSIONS: Counseling is an important part of successful IYCF. The method of counseling is by the counselor visiting pregnant women/mothers of toddlers/caregivers directly and face to face. Benefit of giving counseling for IYCF is that mothers will know nutritional status of their children.